On Moving Contacts in On-Load Tap Changers - Hillergren, Johan; Lindahl, Martin (My University, 2010)
This is a Master's thesis in Applied Physics. The primary topic of the thesis is to develop an accelerated life test for the moving contacts in on-load tap changers, simulating the wear of 30 years use regarding oxidation and coking. The secondary topic is to examine the surface structure of silver contacts to aid in understanding how silver iodide contacts can have the superb electrical properties of silver contacts, but with much better frictional properties. The accelerated life test simulates the wear on the contacts of the OLTC, stemming from oxidation, coking and thermal deformations, during the course of 30 years in only 30 days. The thesis begins with a theoretical background on electrical contacts, tap changers and accelerated testing. It then treats the theoretical derivation of the test parameters. An evaluation test is set up and performed to evaluate the feasability and merit of the test. The results are promising, as the contacts performed as expected with the contact pairs copper/brass performing poorly, copper/silver performing acceptedly and silver/silver performing exceptionally. The surface structure examination begins with a wear process, where sliding silver and silver iodide contacts are worn using an on-load tap changer operating 400 times to create a worn track on the contacts. The contact surfaces are then observed in a scanning electron microscope in search for pores and crevices where iodide could accumulate. These pores and crevices are found, although the accumulation of silver iodide in these not can be proven at this point. That the pores now are shown to exist on the surfaces is a step in the right direction regarding the accumulation hypothesis. It is a necessary but not sufficient criterion for the accumulation hypothesis to be true.
Keywords: Fysik; Physical Sciences